The Effects of Tropospheric Bias on Deformation Monitoring of MT. Guntur using GPS Survey Method - Hasanuddin Z. Abidin; O. Yolanda; I. Meilano; M.A. Kusuma; D. Muhardi; B. Setyadi; J. Kahar; O.K. Suganda; R. Sukhyar; T. Tanaka (Journal of Mathematical and Fundamental Sciences, 1998)
Pemantauan deformasi gunung api yang andal menuntut ketelitian yang tinggi, yaitu sampai level keteliatian mm untuk kasus gunung api yang tengah 'bangkit' kembali. Konsekuensinya adalah kesalahan dan bias yang dapat mengurangi ketelitian dalam penentuan posisi dengan satelit GPS harus dieliminasi dana tau direduksi, seperti kesalahan yang disebabkan oleh bias troposfer. Pada kasus pemantauan deformasi gunung api dengan metode survei GPS, karena adanya perbedaan tinggi yang cukup besar dan variatif antara titik-titik dalam jaringan, maka efek kesalahan bias troposfer tidak sepenuhnya dapat direduksi dengan proses pengurangan data (differencing). Residu (sisa) bias troposter ini harus dikoreksi agar tingkat keteliatian yang dituntut oleh sistem pemantauan deformasi gunung api dapat tetap tercapai. Pada makalah ini akan dibahas efek bias troposfer pada pemantauan deformasi gunung api. Pembahasan didasarkan pada hasil yang diperoleh dari pemantauan deformasi G. Guntur (Garut, Jawa Barat) dengan metode survei GPS. The Effects of Tropospheric Bias on Deformation Monitoring of MT. Guntur using GPS Survey MethodA reliable volcano deformation monitoring requires a high positioning accuracy, i.e. up to mm level in the case of reawakening volcanoes. As a consequence of this requirement, the errors and biases affecting the GPS positioning accuracy has to be eliminated or reduced, which one of them is the tropospheric bias. In the case of volcano deformation monitoring using the GPS survey method, due to a relatively large altitude variation in the stations altitude, the effects of tropospheric bias could not be effectively reduced by the differencing process. In order to meet the accuracy requirement of volcano deformation monitoring system, this residual tropospheric bias, therefore, has to be somehow corrected or taken into account. In this paper, the effects of tropospheric bias on the volcano deformation monitoring will be discussed. The discussion is based on the results from the deformation monitoring of Guntur volcano in Garut, West Java, by using repeated GPS surveys.